Increased Demand Determinants Analysis of Patient Care Class BPJS (Operator Of Social Security Agency) Non PBI (Beneficiaries Fee) Royal Prima Hospital Year 2018 - Tarigan, Antje Irmella; Ginting, Daniel; Brahmana, Netti Etalia (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
The decision to choose the promotion of the next treatment is a petition which shows up to the health care in the National Health Insurance Indonesian era. The stipulation to promote to the next level of treatment is regulated by Presidential Regulation Number 12 in 2013 about health insurance chapter 24. In this research, the researcher found roommates Several factors influence the petition of health care. This research aims to determine the petition of the promotion to the next level of treatment to the BPJS non PSB Patients at the Royal Hospital Prima in 2018. This research uses cross sectional approach to 90 respondents. The result of this research shows us the which the significant factors influence the selection of the promotion to the next level such as the treatment of hospital facilities, the service facilities, the cost, the ease of information and the perception toward the diseases. The hospital facilities are the most decisive factor toward the petition of the promotion to the next level of treatment to the BPJS non PBI Patients at Royal Prima in 2018. It means that the facilities of the Royal Prima hospital will influence 3697 times of increasing the petition of BPJS non PBI Patients at Royal Prima hospital in 2018. In conclusion, the hospital facilities are the most decisive factor of increasing the petition of BPJS non PBI Patients to the next level of treatment at the Royal Prima Hospital in 2018. The researcher suggests to the management of hospital to provide affordable prices of VIP class.